Restoring social deficits in IRSp53-deleted mice: chemogenetic inhibition of ventral dentate gyrus Emx1-expressing cells - Su Hyun Kim; Bomee Lee; Seong Mi Lee; Yangsik Kim (Translational Psychiatry, 2024)
Abstract IRSp53 is a synaptic scaffold protein reported to be involved in schizophrenia, autism spectrum disorders, and social deficits in knockout mice. Identifying critical brain regions and cells related to IRSp53 deletion is expected to be of great help in the treatment of psychiatric problems. In this study, we performed chemogenetic inhibition within the ventral dentate gyrus (vDG) of mice with IRSp53 deletion in Emx1-expressing cells (Emx1-Cre;IRSp53 flox/flox). We observed the recovery of social deficits after chemogenetic inhibition within vDG of Emx1-Cre;IRSp53 flox/flox mice. Additionally, chemogenetic activation induced social deficits in Emx1-Cre mice. CRHR1 expression increased in the hippocampus of Emx1-Cre;IRSp53 flox/flox mice, and CRHR1 was reduced by chemogenetic inhibition. Htd2, Ccn1, and Atp61l were decreased in bulk RNA sequencing, and Eya1 and Ecrg4 were decreased in single-cell RNA sequencing of the hippocampus in Emx1-Cre;IRSp53 flox/flox mice compared to control mice. This study determined that the vDG is a critical brain region for social deficits caused by IRSp53 deletion. Social deficits in Emx1-Cre;IRSp53 flox/flox mice were recovered through chemogenetic inhibition, providing clues for new treatment methods for psychiatric disorders accompanied by social deficits.